The art of LEGO Mindstorms NXT-G programming - Griffin, Terry, 1962- (No Starch Press, 2010)
"The LEGO MINDSTORMS software and its NXT-G programming language are powerful tools that make it easy to write custom programs for your robots. NXT-G is a great first programming language, but that doesn't mean it's easy to understand--at least not right away. In The Art of LEGO MINDSTORMS NXT-G Programming, author and experienced software engineer Terry Griffin explains how to program MINDSTORMS robots with NXT-G. You'll learn how to work with the core parts of the NXT-G language, such as blocks, data wires, files, and variables, and see how these pieces can work together. You'll also learn good programming practices, bad habits to avoid, and useful debugging strategies"--Page 4 of cover.